2011
DOI: 10.1002/adsc.201100051
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Route to Both Enantiomers of allo‐Threonine by Simultaneous Amino Acid Racemase‐Catalyzed Isomerization of Threonine and Crystallization

Abstract: We present an efficient method for the production of d-and l-allo-threonine (allo-Thr) with very high purity by enzymatic isomerization of l-or d-threonine (Thr) and simultaneous crystallization. Isomerization of Thr to allo-Thr is catalyzed by a purified amino acid racemase (AArac12996) from Pseudomonas putida NBRC12996, which can easily be obtained from a recombinant E. coli strain by secretion into the medium and subsequent anion exchange chromatography. Crystallization of d-and l-allo-Thr was performed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…For amino acid compounds, in our previous work, we performed TCID of asparagine monohydrate in the presence of immobilized AArac12996 . Hence, the epimerization of Thr to aThr using immobilized AArac12996 should also be possible as immobilized AArac12996 catalyzes an epimerization at the α-C atom, as already confirmed by Würges et al…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…For amino acid compounds, in our previous work, we performed TCID of asparagine monohydrate in the presence of immobilized AArac12996 . Hence, the epimerization of Thr to aThr using immobilized AArac12996 should also be possible as immobilized AArac12996 catalyzes an epimerization at the α-C atom, as already confirmed by Würges et al…”
Section: Introductionsupporting
confidence: 65%
“…There are several chemical and enzymatic syntheses to produce aThr; however, the direct synthesis of allothreonine via chemical and enzymatic approaches requires multiple steps of synthesis. Besides direct synthesis of aThr, the epimerization of Thr at α-C or β-C atoms is an alternative way to achieve a mixture of Thr and aThr. After epimerization, the separation of aThr from the mixture is essential. , For instance, Würges et al demonstrated a method for aThr production from Thr by a combination of enzymatic epimerization of Thr to aThr using AArac12996 and simultaneous crystallization in a suspension of Thr.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to chemical racemizing agents, several amino acid racemases are available, which allow for racemization of the amino acid at mild temperatures. Examples include alanine racemase from Schizosaccharomyces pombe, arginine racemase from Pseudomonas graveolens, glutamate racemase from Pseudomonas pentosaceus, serine racemase from rat brain, and amino acid racemases from Pseudomonas putida (P. putida).…”
Section: Introductionmentioning
confidence: 99%
“…38,39 Another example is the combination of preferential crystallisation with enzymatic in situ racemisation, as exemplified for L-asparagine 40 and allo-threonine. 41 3.6. Ligases (EC 6)…”
Section: Isomerases (Ec 5)mentioning
confidence: 99%